Study on mechanical properties of high damping viscoelastic dampers. Issue 14 (October 2019) - Chen, Yun; Chen, Chao; Ma, Qianqian; Jiang, Huanjun; Wan, Zhiwei
The mechanical properties of the viscoelastic damper made of high damping rubber produced in China are investigated in order to provide the basis for its application. At first, the test on material properties of high damping rubber is conducted. The Mooney–Rivlin model, the Yeoh model and the Prony series are applied for simulating the nonlinear behavior of the high damping rubber with the aid of software ABAQUS. Then, three viscoelastic dampers with different sizes are tested under cyclic loading. The effects of strain amplitude and loading frequency on hysteretic behavior of dampers are analyzed. Viscoelastic dampers possess large deformation capability, stable energy-dissipation capacity and good fatigue-resisting property. The effect of strain amplitude is much more significant than loading frequency. The hysteretic behavior of the dampers is simulated by the Bouc–Wen model and the model of the equivalent stiffness and damping, respectively. The prediction results by using the Bouc–Wen model are in good agreement with the experimental results, which indicates that the Bouc–Wen model is applicable to simulate the mechanical properties of high damping viscoelastic dampers with a wide range of shear strain. As to the model of equivalent stiffness and damping, it has the advantages of clear concept and simple calculation. However, the good accuracy of prediction can be obtained only when the shear strain is not greater than 60%.